Efecto de la aplicación de Dosis de Silicio más Abonos Orgánicos en la poda de rehabilitación en plantas de Café variedad Catimor en el distrito de Alonso de Alvarado Roque - provincia de Lamas - García Bartra, Dany (2012)
This research paper "Effect of dose application of organic fertilizers in silicon more pruning rehabilitation Catimor variety coffee plants in the district of Alonso de Alvarado Roque - Lamas province", aimed to: compare the effect of applying a solution of mineral and organic acids, enriched with three (03) of silicon dose in admixture with a organo-mineral fertilizer (standard formulation), on the rehabilitation pruning Catimor coffee variety and determine the dose of formulation silicon applied to better contribute to the induction of shoot growth in the coffee plant, after pruning rehabilitation. The present research design used randomized complete block with three replications and 5 treatments, making a total of 15 experimental units, where we studied the effect of a solution enriched silicon more organic fertilizers. The treatments were: Coffee, Variety "Catimor" as an indicator crops, treatments were combinations of organic-mineral fertilizer (standard formulation) comprising: island guano, rock phosphate, potassium sulfate, ulexite, magnecal, sulfate copper, zinc sulfate, manganese sulfate (AO) and a solution of mineral and organic acids enriched with three (03) Si doses (5, 10, 15 cc silicon / plant / year), an absolute control (T0) , who did not receive any application. The most significant findings were: application treatments enriched silicon solution: T2 (5 cc), T3 (10 cc) and T4 (15 cc) were more precocious sprouting after pruning coffee rehabilitation, with no statistical significance between them. T4 (15 cc Si) was the earliest sprouting to 30.20 days than T0 (absolute control) and T1 (AO without Si), which sprang up to 33.42 and 34.02 days, respectively. The dose 15 cc of Si (T4), induced the highest number of shoots / plant by 10.03 on average outbreaks, outperforming all other treatments T0, T3, T1, T2. The best answers that were given. This again demonstrates the benefits of Silicon in this case favoring the appearance of a greater number of branches per outbreak after pruning. The trend that treatments with higher doses of silicon are among the most outstanding in the number of leaves / shoot, while the absolute control and the lowest dose of silicon rank lowest. The further development of leaf area had T4 treatment (15 cc Si) with 79.68 cm2, followed by T3 (10 cc Si) with leaf area of 75.5 cm2 on average. Doses of silicon formulation helped to better growth and induction of shoot development in the coffee plant, after pruning rehabilitation treatments were T4 (15 cc Si) and T3 (10 cc Si).